Erosion Analysis in the Mrica Reservoir Catchment Area in Indonesia using the Soil Erosion Status Method - Beny Harjadi (Forum Geografi, 2021)
The reservoir catchment area (RCA) of Mrica in Banjarnegara district is a powerplant in Central Java with a capacity of 184.5 MW. Mrica Dam, also called the dam of Great Commander General Sudirman, has seen its functions gradually decrease due to sedimentation from massive erosion that has occurred in the upland regions. RCA Mrica, with the upland area in Wonosobo district, has an area of 93,546.4 hectares, consisting of six sub-watersheds, Lumajang, Serayu upstream, Begaluh, Serayu, Tulis and Merawu. In 2017, sedimentation in the dam reached 238,236,588.20 m3/year, resulting from an erosion rate of 524,948.33 tons/year. In light of this serious erosion problem in the Mrica RCA, this study aims to estimate the distribution of the erosion level, categorised as slight, moderate and severe, using the SES (soil erosion status) formula. SES was calculated by mapping the level of each influential aspect: aspect, drainage, land cover, slope and soil texture. The calculation used SRTM (Shuttle Radar Topography Mission) satellite imagery and 2017 Landsat TM7 images. The results show slight erosion (50 tons/ha/year) in 1,468.7 ha (1.6%); moderate erosion (50-100 tons/ha/yr) in 56,258.8 ha (60.1%); and severe erosion ( 100 tons/ha/year) in 35,818.9 ha (38.29%). Sampling in the field took into account the slope class of nine classes and was repeated three times, so the number of samples taken in the field was 27. From field visits to the 27 location points, there was conformity in the results of the sensing analysis is much more than 85%”.  The results of the erosion calculation using the SES method showed severe erosion of 27.9% (26,137 ha); moderate erosion of 70.2% (65,679 ha); and slight erosion =of 1.8% (1,731 ha).  Further erosion calculation using the SES method needs to be compared with calculation using other methods.